Aligning Alternative Assessment with Curriculum Design and Teaching Practices: The Case of Communicative English Skills Course at Three Ethiopian Universities - Minda Hirpassa Motuma; Chaka Chaka (Journal of English Language Studies, 2023)
The current study set out to investigate the alignment of alternative assessment (AA) with the communicative English skills course (CESC) curriculum design and the CESC teaching practices at three Ethiopian universities. Employing a mixed-methods design, it was guided by three research questions. The study utilised summative content data and quantitative content data, and subjected them to descriptive statistics, and Mann-Whitney U Test and Kruskal-Wallis Test. Some of its main results are worth mentioning. Firstly, out of a total of 632 assessment items in CESC, only 30.22% of them were found to be communicatively using AA, while 69.78% of the items in the module were found to be using traditional assessment (TA). Secondly, the instructors’ assessment practices in CESC were inconsistent with AA, and varied across the three universities and from instructor to instructor. The assessment items were disproportionate to the language objectives in CESC because the instructors mainly devoted more time to assessing reading skills, grammar, and vocabulary knowledge. For example, the correlation coefficients of the assessment items for grammar (0.142), vocabulary (0.139), and reading (0.115) were better aligned with the content items in the CESC module than the assessment items for speaking (0.106), listening (0.017), and writing (0.060). Thirdly, based on the correlation coefficients of the study, the overall alignment between the instructors’ AA items and the communicativeness of the items in CESC (0.1291) was generally very low at the three universities during the study period. To this end, CESC should be designed in such a way as to incorporate complex authentic and challenging learning activities. Fourthly and finally, the alignment between the dimensions of CESC in the Ethiopian higher education context is a new area of engagement. Therefore, there is room for further studies to investigate this issue without which the teaching and the assessment of CESC are likely to be compromised.